Perceived importance of structural factors are associated with the selection of primary care by national health insurance participants - Putu Nitya Nirmala; Pande Putu Januraga; Putu Ayu Indrayathi (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: Primary care are the entry point for health services in an insurance-based health financing system, including the National Health Insurance Program or Jaminan Kesehatan Nasional (JKN) in Indonesia. This study aims to understand the association between structural factors in health service management with primary care selection among JKN participants. Methods: The study used a cross sectional analytic design, conducted with 273 self-paid JKN participants in Denpasar as respondents. The samples were selected using multistage random sampling. Data was collected from April to May 2018 with interviews using a questionnaire covering the characteristics of respondents and perceptions on the importance of health care facilities, the capabilities of health providers, service distance, operational time, availability of drugs and medical equipment. Data analysis was carried out with multinomial logistic regression to determine the structural factors of health service management associated with the selection of primary care. Results: Most respondents (65.9%) chose private clinics, 21.3% chose public health centres (PHCs) and 12.8% chose individual practicing physicians. Multivariate analysis showed that the variables which significantly associated with the selection of primary care among JKN participants were the perceived importance of the health care facilities at PHCs and private clinics, each with AOR=7.83 (95%CI: 2.72–22.54) and AOR=7.18 (95%CI: 2.76–18.68), the perceived importance of the capability of health workers in private clinics with AOR=0.29 (95%CI: 0.12–0.77), the perceived importance of health service time in private clinics with AOR=2.67 (95%CI: 1.05–6.74) and history of health services utilization at private clinics with AOR=4.51 (95%CI: 1.86–10.96). Conclusion: Structural factors are associated with the selection of primary care among JKN participants. Attention to the quality and quantity of structural factors in the management of health services is important to improve the equitable distribution of JKN membership in the registered primary care.